Heat exchangers and tube materials for heat exchangers
By applying specific alloy and zinc content films on the tube body and shell of the heat exchanger, the liquid ratio is controlled, and the problems of degradation of heat exchange performance and poor corrosion protection caused by excessive zinc concentration in single-layer welding sheet-fin materials are solved, achieving more efficient heat exchange and longer service life.
Patent Information
- Application Number
- JP2020213617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-12-23
AI Technical Summary
In the prior art, when using single-layer weld sheet-fin materials, excessive zinc concentration leads to too low fillet potential, resulting in a degradation of heat exchange performance and poor corrosion protection effect.
Using a zinc content film with a zinc content of 1.0% to 4.5 g/m², and a specific alloy is applied to the tube body and shell of the heat exchanger, the control liquid ratio is between 5.0% and 35.0%, to form a strong thermal bonding function through heat treatment.
It effectively suppresses the excessive zinc concentration in fillet, avoids the problem of low fillet potential, extends the service life of the heat exchanger, and improves the heat exchange and corrosion protection performance.
Smart Images

Figure 0007665332000005 
Figure 0007665332000006 
Figure 0007665332000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat exchanger and a heat exchanger tube material and a heat exchanger fin material used therein, and more particularly to a heat exchanger for a room air conditioner, a heat exchanger for a car air conditioner, and a heat exchanger tube material and a heat exchanger fin material used therein. [Background technology]
[0002] Aluminum alloys, which are lightweight and have high thermal conductivity, are often used in aluminum alloy heat exchangers for automobiles, such as evaporators and condensers. The heat exchanger has tubes through which a refrigerant flows and fins for exchanging heat between the refrigerant and the air outside the tubes, and the tubes and fins are joined by brazing. Fluoride-based flux is often used to braze the tubes and fins.
[0003] As described above, tubes used in automotive heat exchangers are joined to fins by brazing in order to perform heat exchange, and for this purpose, a brazing material must be provided on either the fin side or the tube side.
[0004] When the brazing material is provided on the fin side, the fin is produced using a clad material in which the brazing material is clad, but this makes it difficult to reduce the manufacturing costs and material costs.
[0005] On the other hand, in the case of providing a brazing material on the tube side, a technology has been proposed in which a flux layer containing Si (silicon) powder, Zn-containing flux, and a binder is formed on the outer surface of the tube (Patent Document 1). The flux layer having the above composition allows the brazing material components, Zn, and flux components to be simultaneously deposited in a single deposition process. In addition, since there is no need to provide a brazing material on the fin side, the fins can be manufactured using bare fin material. As a result, costs can be reduced.
[0006] However, in the method of Patent Document 1, Si powder is attached to the surface of the tube material, and the tube material is brazed using the brazing filler produced by eutectic melting between the Si powder and the surface layer of the tube material during the heating process due to brazing heating. This makes it difficult to make the tube material thin, and if coarse Si powder is mixed in, problems arise in that the tube will become dented or will melt and become perforated.
[0007] Therefore, Patent Document 2 describes a method of using a single-layer brazing sheet instead of the above-mentioned clad material brazing sheet in order to omit the processes of manufacturing the brazing sheet and manufacturing and applying the powder brazing material.
[0008] By using the method of Patent Document 2, brazing is possible using a single layer brazing sheet for fin materials, eliminating the need to apply brazing material to both the fin material and the tube material, allowing for significant cost reductions. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication WO2011 / 090059 [Patent Document 2] International Publication WO2014 / 196183 Summary of the Invention [Problem to be solved by the invention]
[0010] However, in the method of Patent Document 2, the amount of liquid phase generated is relatively small compared to conventional methods such as the method of Patent Document 1 and brazing using a clad fin material clad with a brazing material, and the cross-sectional area of the fillet formed between the fin and the tube is small.
[0011] Therefore, when a single-layer brazing sheet fin is combined with a Zn-sprayed tube material that has been conventionally used for heat exchangers, the Zn concentration per unit cross-sectional area in the fillet after brazing will be higher than with the conventional method, and there was a concern that preferential corrosion of the fillet would occur because the potential of the fillet would be the most base.
[0012] When preferential corrosion of the fillets occurs, the fillets, i.e., the joints between the fins and the tubes, disappear early, causing the fins to fall off from the tube surfaces, reducing heat exchange performance and causing the fins to no longer protect the tubes from corrosion.
[0013] Therefore, the object of the present invention is to provide a heat exchanger obtained using a single-layer brazing sheet fin material, which suppresses excessive Zn concentration in the fillet and prevents the fillet potential from becoming excessively base, thereby allowing the fins to remain on the tubes for a long period of time and having excellent heat exchange performance and corrosion prevention performance, and to provide tube materials and fin materials for heat exchangers to be used therefor. [Means for solving the problem]
[0014] The above problems are solved by the present invention described below. That is, the present invention (1) is a heat exchanger having an aluminum alloy tube through which a working fluid flows and an aluminum alloy fin metallically joined to the tube, The tube is made of an aluminum alloy and has a tube body and a thickness of 1.0 to 4.5 g / m2 formed on the outer surface of the tube body. 2 and a heat exchanger tube material having a Zn-containing membrane containing Zn, The fin is made of an aluminum alloy and is formed using a heat exchanger fin material having a single layer thermal bonding function at a temperature at which the liquid phase ratio is 5.0% or more and 35.0% or less. The present invention provides a heat exchanger characterized by the above.
[0015] The present invention (2) provides a heat exchanger according to (1), characterized in that the aluminum alloy forming the tube body is an aluminum alloy containing 0.10 to 1.20 mass% Mn, a Ti content of 0.10 mass% or less, and the remainder being Al and unavoidable impurities.
[0016] The present invention (3) also provides a heat exchanger according to (2), characterized in that the aluminum alloy forming the tube body further contains one or more elements selected from the group consisting of 0.60 mass % or less of Cu, 0.70 mass % or less of Si, and 0.50 mass % or less of Fe.
[0017] The present invention (4) also provides the heat exchanger according to any one of (1) to (3), wherein the Zn-containing film contains flux powder made of a compound containing Zn.
[0018] The present invention (5) also provides a heat exchanger according to (4), wherein the flux powder is made of a K-Zn-F based compound.
[0019] The present invention (6) also provides the heat exchanger according to any one of (1) to (3), wherein the Zn-containing film contains pure Zn powder.
[0020] The present invention (7) also provides the heat exchanger according to any one of (1) to (3), wherein the Zn-containing film is a zinc-sprayed film formed by zinc spraying.
[0021] The present invention (8) provides a heat exchanger according to any one of (1) to (7), characterized in that the aluminum alloy forming the heat exchanger fin material is an aluminum alloy containing 1.00 to 5.00 mass% Si, 0.05 to 2.00 mass% Mn, with an Fe content of 2.00 mass% or less, and the remainder being Al and unavoidable impurities.
[0022] The present invention (9) also provides a heat exchanger according to (8), characterized in that the aluminum alloy forming the heat exchanger fin material further contains one or more selected from 2.00 mass% or less of Mg, 1.50 mass% or less of Cu, 6.00 mass% or less of Zn, 0.30 mass% or less of Ti, 0.30 mass% or less of V, 0.30 mass% or less of Zr, 0.30 mass% or less of Cr, and 2.00 mass% or less of Ni.
[0023] The present invention (10) also provides a heat exchanger according to (8) or (9), characterized in that the aluminum alloy forming the heat exchanger fin material further contains one or more selected from 0.30 mass% or less of Sn, 0.30 mass% or less of In, 0.10 mass% or less of Be, 0.10 mass% or less of Sr, 0.10 mass% or less of Bi, 0.10 mass% or less of Na, and 0.50 mass% or less of Ca.
[0024] The present invention (11) is a tube material for a heat exchanger according to claim 1, A tube material body is made of an aluminum alloy containing 0.10 to 1.20 mass% Mn, a Ti content of 0.10 mass% or less, and the balance being Al and unavoidable impurities, and a ferroelectric thin film is formed on the outer surface of the tube material body, and the ferroelectric thin film has a density of 1.0 to 4.5 g / m in atomic terms. 2 and a Zn-containing film containing Zn.
[0025] The present invention (12) also provides a heat exchanger tube material according to (11), further comprising one or more elements selected from the group consisting of 0.60 mass % or less of Cu, 0.70 mass % or less of Si, and 0.50 mass % or less of Fe.
[0026] The present invention (13) also provides a heat exchanger tube material according to (11) or (12), characterized in that the Zn-containing film contains flux powder made of a compound containing Zn.
[0027] The present invention (14) also provides a heat exchanger tube material according to the above (13), characterized in that the flux powder is made of a K-Zn-F based compound.
[0028] The present invention (15) also provides a heat exchanger tube material according to (11) or (12), characterized in that the Zn-containing film contains Zn powder.
[0029] The present invention (16) also provides a heat exchanger tube material according to (11) or (12), characterized in that the Zn-containing film is a zinc sprayed film formed by a zinc sprayed layer.
[0030] The present invention (17) is a fin material for a heat exchanger according to claim 1, An aluminum alloy containing 1.00 to 5.00 mass% Si, 0.05 to 2.00 mass% Mn, an Fe content of 2.00 mass% or less, and the remainder being Al and unavoidable impurities; The material has a thermal bonding function in a single layer at a temperature where the liquid phase ratio is 5.0% or more and 35.0% or less. The present invention provides a fin material for a heat exchanger, characterized in that
[0031] The present invention (18) also provides a heat exchanger fin material according to (17), characterized in that the aluminum alloy further contains one or more selected from the group consisting of 2.00 mass% or less Mg, 1.50 mass% or less Cu, 6.00 mass% or less Zn, 0.30 mass% or less Ti, 0.30 mass% or less V, 0.30 mass% or less Zr, 0.30 mass% or less Cr, and 2.00 mass% or less Ni.
[0032] The present invention (19) also provides a heat exchanger fin material according to (17) or (18), characterized in that the aluminum alloy further contains one or more selected from the group consisting of 0.30 mass% or less Sn, 0.30 mass% or less In, 0.10 mass% or less Be, 0.10 mass% or less Sr, 0.10 mass% or less Bi, 0.10 mass% or less Na, and 0.50 mass% or less Ca.
[0033] The present invention (20) is a heat exchanger having an aluminum alloy tube through which a working fluid flows, and an aluminum alloy fin metallically joined to the tube, At least, a tube body made of an aluminum alloy and a ferrite layer formed on the outer surface of the tube body, the ferrite layer having an atomic ratio of 1.0 to 4.5 g / m 2 and a Zn-containing film containing Zn, and a heat exchanger fin material made of an aluminum alloy and having a single-layer thermal bonding function at a temperature at which the liquid phase ratio of the heat exchanger fin material is 5.0% or more and 35.0% or less, and then the resulting combination is heated at a temperature at which the liquid phase ratio of the heat exchanger fin material is 5.0% or more and 35.0% or less to bond the heat exchanger tube material and the heat exchanger fin material. The present invention provides a heat exchanger characterized by the above. Effect of the Invention
[0034] According to the present invention, a heat exchanger is provided using a single-layer brazing sheet fin material, and by suppressing excessive Zn concentration in the fillet and preventing the fillet potential from becoming excessively base, the fins remain on the tubes for a long period of time, and the heat exchanger has excellent heat exchange performance and corrosion prevention performance.The present invention also provides tube materials and fin materials for heat exchangers to be used therefor. [Brief description of the drawings]
[0035] [Figure 1] Schematic phase diagram of an Al-Si alloy, which is a typical binary eutectic alloy. [Diagram 2] FIG. 1 is an explanatory diagram showing a mechanism for generating a liquid phase in an aluminum alloy forming the heat exchanger fin material according to the present invention, in a bonding process using the heat exchanger fin material according to the present invention. [Diagram 3] FIG. 1 is an explanatory diagram showing a mechanism for generating a liquid phase in an aluminum alloy forming the heat exchanger fin material according to the present invention, in a bonding process using the heat exchanger fin material according to the present invention. [Figure 4] Schematic phase diagram of an Al-Si alloy, which is a typical binary eutectic alloy. [Diagram 5] FIG. 2 is a schematic diagram showing an assembled state of a mini-core produced in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The heat exchanger of the present invention is a heat exchanger having an aluminum alloy tube through which a working fluid flows, and an aluminum alloy fin metallically joined to the tube, The tube is made of an aluminum alloy and has a tube body and a thickness of 1.0 to 4.5 g / m2 formed on the outer surface of the tube body. 2 and a heat exchanger tube material having a Zn-containing membrane containing Zn, The fin is made of an aluminum alloy and is formed using a heat exchanger fin material having a single layer thermal bonding function at a temperature at which the liquid phase ratio is 5.0% to 35.0%. This is a heat exchanger characterized by the above.
[0037] The heat exchanger of the present invention has at least tubes made of an aluminum alloy through which a working fluid flows, and fins made of an aluminum alloy metallically joined to the tubes. In the heat exchanger of the present invention, the tubes are formed using the heat exchanger tube material of the present invention, and the fins are formed using the heat exchanger fin material of the present invention. That is, the tubes of the heat exchanger of the present invention are formed by heating the heat exchanger tube material of the present invention at a predetermined temperature and joining it to the heat exchanger fin material of the present invention, and the fins of the heat exchanger of the present invention are formed by heating the heat exchanger fin material of the present invention at a predetermined temperature and joining it to the heat exchanger tube material of the present invention.
[0038] In other words, the heat exchanger of the present invention is obtained by combining at least the heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention, and then heating the resulting combination at a temperature at which the liquid phase ratio of the fin material is 5.0% or more and 35.0% or less, preferably by heating the region of 400°C or more at an average heating rate of 10°C / min, holding it at 600°C±10°C for 3 to 5 minutes, and cooling it to 100°C or less, thereby joining the heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention.
[0039] The heat exchanger tube material according to the present invention has a tube body made of an aluminum alloy and a Zn-containing film formed on the outer surface of the tube body. The heat exchanger tube material according to the present invention refers to the tube material before being joined to a fin material, i.e., before being heated and joined.
[0040] The shape of the tube body is not particularly limited and is appropriately selected according to the application and required characteristics. The tube body may be an extruded multi-hole tube formed by extrusion processing and having a plurality of refrigerant flow paths inside. The tube body may also be in a cylindrical shape or the like. The tube body may be formed by cutting a plate material formed by rolling processing to a predetermined width, forming a cylindrical shape by roll forming, forming a pipe shape by high frequency welding or laser welding, and further forming a flat tube shape by roll forming. When the plate material formed by rolling processing is processed to form the tube body, a laminated material consisting of an aluminum alloy tube body core material and a sacrificial anode material clad on the outer surface side of the core material can also be used as the plate material for the tube body. When the plate material formed by rolling processing is processed to form the tube body, a laminated material consisting of an aluminum alloy tube body core material and a brazing material clad on the inner surface side of the core material can also be used as the plate material for the tube body. In this case, a fin material made of an aluminum alloy can be corrugated and inserted into the tube to form an inner fin type tube.
[0041] The chemical composition of the aluminum alloy forming the tube body is not particularly limited, but an aluminum alloy containing 0.10 to 1.20 mass % Mn, 0.10 mass % or less Ti, and the balance being Al and unavoidable impurities is preferred.
[0042] The aluminum alloy forming the tube body may contain Mn. When the aluminum alloy forming the tube body contains Mn, the Mn content of the aluminum alloy forming the tube body is 0.10 to 1.20 mass%. Mn has the effect of improving strength by dissolving in the Al (aluminum) matrix. At the same time, it also has the effect of making the potential noble. When the Mn content of the aluminum alloy forming the tube body is within the above range, a sufficient strength improvement effect and a potential noble effect in the deep part of the tube can be obtained. On the other hand, if the Mn content of the aluminum alloy forming the tube body is less than the above range, there is a concern that the desired strength cannot be satisfied. In addition, if the Mn content of the aluminum alloy forming the tube body exceeds the above range, Al-Mn precipitates are generated in the matrix in a process before the hot working described below, which inhibits the movement of grain boundaries, making the crystal structure after brazing fine, which may cause brazing defects such as erosion during brazing, and further, the workability in extrusion processing or rolling processing may decrease, which may decrease the productivity of the tube body. The Mn content of the aluminum alloy forming the tube body is preferably 0.10 to 1.20 mass % from the viewpoint of achieving all of the strength, brazing quality, and productivity.
[0043] The aluminum alloy forming the tube body may contain Ti. When the aluminum alloy forming the tube body contains Ti, the Ti content of the aluminum alloy forming the tube body is 0.10 mass% or less. Ti is added to the aluminum alloy for the purpose of making the structure finer during casting. When the Ti content of the aluminum alloy forming the tube body is within the above range, a uniform metal structure can be obtained after extrusion or rolling. On the other hand, when the Ti content of the aluminum alloy forming the tube body exceeds the above range, there is a risk that large crystals are generated during casting, making it difficult to manufacture a healthy tube body. In addition, in the case of an extruded multi-hole tube, there is a concern that the crystallized Ti generates friction with the die, reducing productivity and tool life, and in the case of a rolled material, there is a concern that the crystallized Ti may cause cracks during roll forming. The Ti content of the aluminum alloy forming the tube body is preferably 0.001 to 0.05 mass%.
[0044] The aluminum alloy forming the tube body may contain Cu. When the aluminum alloy forming the tube body contains Cu, the Cu content of the aluminum alloy forming the tube body is 0.60 mass% or less, preferably 0.20 to 0.60 mass%. Cu has the effect of improving strength by dissolving in the Al (aluminum) parent phase. At the same time, it also has the effect of making the potential noble. When the Cu content of the aluminum alloy forming the tube body is within the above range, a sufficient strength improvement effect and a potential noble effect in the deep part of the tube can be obtained. On the other hand, when the Cu content of the aluminum alloy forming the tube body exceeds the above range, Al-Cu precipitates are generated, which may impair the corrosion resistance of the tube. When Cu is added, the Cu content of the aluminum alloy forming the tube body is more preferably 0.20 to 0.50 mass% from the viewpoint of achieving all of the strength, brazing quality, and productivity. When a lower Cu content is preferable, the Cu content of the aluminum alloy forming the tube body is preferably 0.20 mass % or less, and particularly preferably 0.05 mass % or less.
[0045] The aluminum alloy forming the tube body may contain Si. When the aluminum alloy forming the tube body contains Si, the Si content of the aluminum alloy forming the tube body is 0.70 mass% or less, preferably 0.20 to 0.70 mass% or less. Si has the effect of improving strength by dissolving in the Al (aluminum) matrix or forming AlMnSi precipitates with Mn. When the Si content of the aluminum alloy forming the tube body is within the above range, a sufficient strength improvement effect can be obtained. On the other hand, when the Si content of the aluminum alloy forming the tube body exceeds the above range, the deformation resistance during hot working is excessively increased, the workability in extrusion processing or rolling processing is reduced, and the productivity of the tube body may be reduced. The Si content of the aluminum alloy forming the tube body is preferably 0.30 to 0.70 mass% from the viewpoint of achieving all of the strength, brazing quality, and productivity. When a smaller Si content is preferable, the Si content of the aluminum alloy forming the tube body is preferably 0.30 mass% or less, more preferably 0.20 mass% or less.
[0046] The aluminum alloy forming the tube body is allowed to contain Fe to the extent that it does not affect the effects of the present invention. When the aluminum alloy forming the tube body contains Fe, the Fe content of the aluminum alloy forming the tube body is preferably 0.50 mass% or less, and particularly preferably 0.40 mass% or less.
[0047] The Zn-containing film is formed on the outer surface of the tube body. Examples of the Zn-containing film include a Zn-containing film containing a flux powder made of a compound containing Zn, a Zn-containing film containing pure Zn, and a zinc-sprayed film formed by zinc spraying. The Zn-containing film refers to a film containing zinc element, and in the Zn-containing film, the zinc element exists in the form of metallic zinc or zinc ions.
[0048] The Zn-containing film containing the flux powder made of a compound containing Zn contains at least the flux powder made of a compound containing Zn and a binder. The Zn-containing film containing the flux powder made of a compound containing Zn is formed by, for example, mixing and stirring the flux powder made of a compound containing Zn, the binder, and, if necessary, the flux powder made of a compound not containing Zn, in a solvent to prepare a paste-like paint, and then applying the paint to the surface of the tube body by a roll coating method or the like, and then drying the paint. For example, an acrylic resin or a urethane resin can be used as the binder. For the solvent, water, or water and alcohols such as ethanol and isopropyl alcohol, alkyl ether alcohols such as 3-methoxy-3-methyl-1-butanol, ketones such as methyl ethyl ketone, etc. can be used.
[0049] The Zn-containing compound constituting the flux powder is preferably a K-Zn-F based compound, such as KZnF3.
[0050] The binder is not particularly limited, and a binder that can be used to form a film containing flux powder on the surface of an aluminum alloy material in the manufacture of an aluminum alloy heat exchanger is appropriately selected.
[0051] The Zn-containing film containing pure Zn powder contains at least pure Zn powder and a binder. Note that pure Zn refers to Zn metal with a purity of 99% by mass or more. The Zn-containing film containing pure Zn powder is formed, for example, by mixing and stirring pure Zn powder, a binder, and, if necessary, a flux powder made of a compound containing Zn or a flux powder made of a compound not containing Zn, in a solvent to prepare a paste-like paint, and then applying the paint to the surface of the tube body by a roll coating method or the like, and then drying.
[0052] The binder is not particularly limited, and a binder that can be used to form a film containing pure Zn powder on the surface of an aluminum alloy material in the production of an aluminum alloy heat exchanger is appropriately selected.
[0053] The zinc sprayed film formed by zinc spraying is formed by carrying out Zn spraying on the outer surface of the tube body. The Zn spraying method is not particularly limited, and a conventional spraying method is appropriately used. For example, a method is mentioned in which two Zn wires are brought close to each other, a high voltage current is applied, an arc discharge is caused between the Zn wires, the tip of the Zn wire is melted, the Zn is blown off by spraying a high pressure inert gas, and the tip is passed through the tube body, so that the molten Zn adheres to the outer surface of the tube body. As the element wire used for spraying, a pure Zn wire is preferably used because it is easy to manufacture. In addition, by feeding the Zn wire sequentially as it melts, the arc discharge can be continued, so that a uniform zinc sprayed film can be formed continuously in the longitudinal direction.
[0054] The Zn-containing film has an atomic weight of 1.0 to 4.5 g / m 2 , preferably 1.0 to 3.5 g / m 2The Zn content of the Zn-containing film is within the above range, so that Zn concentration in the fillet can be suppressed, and therefore preferential corrosion of the fillet and early fin drop-off can be prevented. On the other hand, if the Zn content in the Zn-containing film is less than the above range, the corrosion protection by Zn on the tube surface becomes insufficient, and early penetration of the tube may occur at the portion between the fins, and if it exceeds the above range, Zn concentration occurs in the fillet when combined with a single-layer brazing sheet fin and heat-bonded, so preferential corrosion of the fillet and early fin drop-off may occur. In the present invention, the Zn content of the Zn-containing film has a large effect on the effect of suppressing Zn concentration in the fillet. In the present invention, the effect of suppressing Zn concentration in the fillet due to the origin of the Zn element, that is, the effect of suppressing Zn concentration in the fillet due to whether the Zn element is attached to the outer surface of the tube body in the state of Zn atoms or in the state of zinc ions, or the effect of suppressing Zn concentration in the fillet due to whether the Zn source is a flux powder made of a compound containing Zn, a pure Zn powder, or a zinc sprayed film, is small. In the present invention, only the amount of Zn in terms of atoms on the surface of the tube body is limited, and the total mass of the Zn-containing film is not limited.
[0055] The heat exchanger tube material according to the present invention may be produced by any method, and for example, it is produced by the method described below.
[0056] In the method for producing a heat exchanger tube material according to the present invention, first, a tube body is produced by extrusion or rolling. In order to manufacture the tube body by extrusion or rolling, it is preferable to use an aluminum alloy that has been homogenized under the following conditions. In the first embodiment of the homogenization treatment, the homogenization treatment is performed by holding an ingot of an aluminum alloy having a predetermined chemical composition at a temperature of 400 to 650 ° C for 2 hours or more. In this case, the coarse crystallized matter formed during casting is decomposed or granulated, and the non-uniform structure such as the segregation layer generated during casting can be homogenized. As a result, the resistance during extrusion can be reduced and the extrudability can be improved. In addition, the surface roughness of the product after extrusion can be reduced. If the holding temperature in the homogenization treatment is less than 400 ° C, there is a risk that coarse crystallized matter or the above-mentioned non-uniform structure will remain, which may lead to a decrease in extrudability and an increase in surface roughness. The higher the holding temperature in the homogenization treatment, the shorter the holding time and the higher the productivity can be. However, if the holding temperature exceeds 650 ° C, there is a risk that the ingot will melt. Therefore, the holding temperature in the homogenization treatment is preferably 400 to 650 ° C, more preferably 430 to 620 ° C. In addition, the holding time in the homogenization treatment is preferably 5 hours or more from the viewpoint of performing sufficient homogenization. On the other hand, if the holding time exceeds 24 hours, the homogenization effect becomes saturated, and it is difficult to obtain an effect commensurate with the holding time. Therefore, the holding time in the homogenization treatment is preferably 5 to 24 hours. The billet or slab that has been subjected to the homogenization treatment is then subjected to hot extrusion, or rolling and roll forming in accordance with a commonly performed process to obtain a tube body. When producing a rolled material by rolling, hot rolling and cold rolling are performed, and intermediate annealing may be added in between as necessary.
[0057] In the method for producing a heat exchanger tube material according to the present invention, Zn is then applied to the outer surface of the tube body obtained as described above by the method described below to form a Zn-containing film, thereby obtaining the heat exchanger tube material according to the present invention.
[0058] Methods for forming a Zn-containing film on the tube body include the above-mentioned (1) method of applying a paste-like paint containing a flux powder made of a Zn-containing compound, a binder, and, if necessary, a flux powder made of a compound that does not contain Zn, to the outer surface of the tube body and drying it, (2) method of applying a paste-like paint containing pure Zn powder, a binder, and, if necessary, a flux powder made of a compound that contains Zn or a flux powder made of a compound that does not contain Zn, to the outer surface of the tube body and drying it, and (3) method of performing zinc spraying on the outer surface of the tube body to form a zinc sprayed film.
[0059] The heat exchanger fin material according to the present invention is made of an aluminum alloy. The heat exchanger fin material according to the present invention refers to the fin material before being joined to a tube material, i.e., before being heated for joining.
[0060] The fin material for heat exchangers according to the present invention has a thermal bonding function in a single layer at a temperature where the liquid phase ratio is 5.0% or more and 35.0% or less. That is, the fin material for heat exchangers according to the present invention is a fin material made of a single-layer brazing sheet.
[0061] Hereinafter, a brazing sheet having a thermal bonding function as a single layer at a temperature where the liquid phase ratio is 5.0% or more and 35.0% or less (hereinafter, also referred to as a single-layer brazing sheet) will be described. The single-layer brazing sheet needs to be bonded at a temperature where the ratio of the mass of the liquid phase generated in the aluminum alloy material to the total mass of the aluminum alloy material (hereinafter referred to as the "liquid phase ratio") is 5% to 35%. If the liquid phase ratio exceeds 35%, the amount of liquid phase generated is too large, and the aluminum alloy material cannot maintain its shape, resulting in significant deformation. On the other hand, if the liquid phase ratio is less than 5%, bonding becomes difficult. The preferred liquid phase ratio is 5 to 30%, and the more preferred liquid phase ratio is 10 to 20%.
[0062] The mechanism of liquid phase generation will be explained. Figure 1 shows a schematic diagram of an Al-Si alloy, a typical binary eutectic alloy. When an aluminum alloy material with a Si concentration of c1 is heated, the liquid phase begins to be generated at a temperature T1 near the eutectic temperature (solidus temperature) Te. Below the eutectic temperature Te, as shown in Figure 2(a), crystal precipitates are distributed in the matrix divided by the grain boundaries. When the liquid phase begins to be generated here, as shown in Figure 2(b), the grain boundaries with a large amount of segregation in the crystal precipitate distribution melt and become liquid phase. Next, as shown in Figure 2(c), the crystal precipitate particles of Si, which is the main additive element component dispersed in the aluminum alloy matrix, and the periphery of the intermetallic compound melt into a spherical shape and become liquid phase. Furthermore, as shown in Figure 2(d), this spherical liquid phase generated in the matrix is redissolved in the matrix with the passage of time and the rise in temperature due to interface energy, and moves to the grain boundaries and surface by diffusion in the solid phase. Next, when the temperature rises to T2 as shown in Figure 1, the amount of liquid phase increases according to the phase diagram. As shown in FIG. 1, in the case of c2 where the Si concentration of one aluminum alloy material is smaller than the maximum solid solubility limit concentration, the liquid phase begins to be generated near the solidus temperature Ts2. However, unlike the case of c1, the structure just before melting may not have crystal precipitates in the matrix as shown in FIG. 3(a). In this case, as shown in FIG. 3(b), the grain boundary first melts and becomes liquid, and then the liquid phase is generated from a location in the matrix where the solute element concentration is locally high as shown in FIG. 3(c). As shown in FIG. 3(d), the spherical liquid phase generated in the matrix is re-dissolved in the matrix with time and temperature increase due to interface energy, as in the case of c1, and moves to the grain boundary or surface by diffusion in the solid phase. When the temperature rises to T3, the amount of liquid phase increases according to the phase diagram. In this way, the bonding in the present invention utilizes the liquid phase generated by partial melting inside the single-layer brazing sheet (the heat exchanger fin material according to the present invention), and can achieve both bonding and shape retention.
[0063] The behavior of the metal structure from the time when the liquid phase is generated until the joining is explained. The single-layer brazing sheet that generates the liquid phase is combined with the aluminum alloy counter material to be joined, and these are heated at a temperature at which the liquid phase ratio is 5.0% to 35.0%. Then, when the joint is observed with a microscope, as described above, a very small amount of liquid phase generated on the surface of the single-layer brazing sheet during joining fills the gap with the aluminum alloy counter material whose oxide film has been destroyed by the action of flux, etc. Next, the liquid phase near the joining interface between the two alloy materials moves into the aluminum alloy counter material, and the crystal grains of the solid phase α phase of the single-layer brazing sheet in contact with the joining interface grow toward the aluminum alloy counter material. Meanwhile, the crystal grains of the aluminum alloy counter material also grow toward the single-layer brazing sheet. Then, the single-layer brazing sheet is joined with a structure in which the structure of the single-layer brazing sheet has penetrated into the aluminum alloy counter material near the joining interface. Therefore, no metal structure other than that of the single-layer brazing sheet and the aluminum alloy counter material is generated at the joining interface.
[0064] On the other hand, when a brazing sheet clad with a brazing material is used to join an aluminum alloy mating material by brazing heat, a fillet is formed at the joint and a eutectic structure is observed, and a different joint structure is formed than when a single-layer brazing sheet is used to join an aluminum alloy mating material by brazing heat. In other words, when a brazing sheet clad with a brazing material is used to join an aluminum alloy mating material by brazing heat, the liquid phase brazing fills the joint and forms a fillet, so that a eutectic structure different from the surrounding area is formed at the joint. Also, when a welding method is used, the joint melts locally, resulting in a metal structure different from that of other parts.
[0065] For this reason, when a single-layer brazing sheet is used to heat-bond to an aluminum alloy mating material, the metal structure of the bonded portion is composed only of both joined materials, or is composed of both joined materials integrated together, which results in a bond structure that differs from that obtained when a brazing sheet clad with solder is used or when welding is used.
[0066] Due to this joining behavior, when a single-layer brazing sheet is used to heat-join an aluminum alloy mating material, there is almost no change in shape near the joining area after the joining process. In other words, when a single-layer brazing sheet is used to heat-join an aluminum alloy mating material, there is almost no change in shape after joining, such as a bead in a welding method or a fillet in a brazing method. Nevertheless, it allows joining by metal bonding, just like welding and brazing methods. For example, when a drawn cup type laminated heat exchanger is assembled using a brazing sheet clad with a brazing material (clad rate of brazing material is 5% on one side), the molten brazing material concentrates on the joint after brazing heating, so the height of the laminated heat exchanger is reduced by 5 to 10%. Therefore, it is necessary to take this reduction into consideration in product design. On the other hand, when a single-layer brazing sheet is used to heat-join an aluminum alloy mating material, there is extremely little dimensional change after joining, making it possible to design products with high precision.
[0067] In the present invention, it is extremely difficult to measure the actual liquid phase ratio during heating of a single-layer brazing sheet. Therefore, the liquid phase ratio specified in the present invention is determined by equilibrium calculation. Specifically, it is calculated from the alloy composition and the maximum temperature reached during heating using thermodynamic equilibrium calculation software such as Thermo-Calc (registered trademark) manufactured by Thermo-Calc Software AB.
[0068] The relationship between the liquidus ratio and temperature will be described based on the phase diagram shown in FIG. 4. FIG. 4 is a modified version of FIG. 1. In FIG. 4, a line that passes through temperature Te and extends parallel to the horizontal axis (hereinafter referred to as "solidus 1"), and a line that defines the boundary with the α phase and extends from the left end of solidus 1 to 660°C on the vertical axis (hereinafter referred to as "solidus 2"), both represent solidus lines. In addition, a line that extends from 660°C on the vertical axis to the lower right and contacts solidus 1 (hereinafter referred to as "liquidus 1"), and a line that defines the boundary with the (Si+liquid phase) and extends from the contact position to the upper right, both represent liquidus lines. Here, the point at temperature T2 is P0, a line is drawn through P0 parallel to the horizontal axis of the figure, and the intersection with liquidus 1 is P1, and the intersection with solidus 2 is P2. An Al-Si alloy with a Si concentration of C1 is in a state where the liquid phase and solid phase coexist at temperature T2, and the Si concentration in the liquid phase is the concentration C at point P1. P1 and the Si concentration in the solid phase is the concentration C P2 The ratio of the mass of the liquid phase to the total mass at temperature T2, that is, the liquid phase rate, is the ratio of the length of the line segment P0 to P2 to the length of the line segment P1 to P2.
[0069] As described above, the liquid fraction can be obtained by drawing a diagram from the alloy components and temperature based on the phase diagrams of binary alloys as shown in Figures 1 and 4. Similarly, for ternary or higher component systems, the liquid fraction can also be obtained by drawing a diagram from the alloy components and temperature based on the phase diagram. It is difficult to represent the phase diagram of a ternary or higher component system as a simple XY plane diagram as in Figure 4, but the liquid fraction can be obtained by computer calculation using Thermo-Calc thermodynamic equilibrium calculation software.
[0070] The chemical composition of the aluminum alloy forming the heat exchanger fin material according to the present invention is not particularly limited as long as it has a thermal bonding function in a single layer at a temperature where the liquid phase ratio is 5.0% or more and 35.0% or less. However, an aluminum alloy containing 1.00 to 5.00 mass% Si, 0.05 to 2.00 mass% Mn, with the balance being Al and unavoidable impurities is preferred.
[0071] The aluminum alloy forming the heat exchanger fin material according to the present invention contains Si. The Si content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 1.00 to 5.00 mass%. Si is an element that generates an Al-Si liquid phase and contributes to bonding. When the Si content of the aluminum alloy forming the heat exchanger fin material is in the above range, Si generates an Al-Si liquid phase and bonding becomes possible. On the other hand, if the Si content of the aluminum alloy forming the heat exchanger fin material is less than the above range, a sufficient amount of liquid phase cannot be generated, the liquid phase does not bleed out much, and bonding becomes incomplete. Also, if the Si content exceeds the above range, the amount of liquid phase generated in the aluminum alloy material increases, so that the material strength during heating is extremely reduced, and it becomes difficult to maintain the shape of the heat exchanger. The Si content of the aluminum alloy forming the heat exchanger fin material according to the present invention is preferably 1.50 to 3.50 mass%, more preferably 2.00 to 3.00 mass%. In addition, since the amount of liquid phase that seeps out increases with the thickness of the plate and the heating temperature, it is preferable to adjust the amount of liquid phase required during heating according to the structure of the heat exchanger to be manufactured by adjusting the required Si content and bonding heating temperature.
[0072] The aluminum alloy forming the heat exchanger fin material according to the present invention contains Mn. The Mn content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.05 to 2.00 mass%, preferably 0.10 to 2.00 mass%, and more preferably 0.30 to 1.50 mass%. Mn is an important additive element that forms an Al-Mn-Si intermetallic compound together with Si, acts as dispersion strengthening, or dissolves in the aluminum parent phase to improve strength by solid solution strengthening. When the Mn content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength of the fin material is increased. On the other hand, if the Mn content of the aluminum alloy forming the heat exchanger fin material is less than the above range, the above effect becomes insufficient, and if it exceeds the above range, coarse intermetallic compounds are easily formed, resulting in low corrosion resistance.
[0073] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Fe. The Fe content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 2.00 mass% or less, preferably 0.10 to 2.00 mass%, more preferably 0.20 to 1.00 mass%. Fe has the effect of improving strength by being slightly dissolved in the matrix, and also has the effect of preventing a decrease in strength, particularly at high temperatures, by dispersing as a crystallized product. If the Fe content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, coarse intermetallic compounds are generated during casting, causing problems in manufacturability, and when the heat exchanger is exposed to a corrosive environment (particularly a corrosive environment in which liquid flows), the corrosion resistance is reduced, and further, the recrystallized crystal grains are refined by heating during bonding, increasing the grain boundary density, resulting in a large change in dimension before and after bonding. In addition, when a smaller Fe content is preferable, the Fe content of the aluminum alloy forming the heat exchanger fin material according to the present invention is preferably 0.50 mass% or less, more preferably 0.30 mass% or less.
[0074] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Mg. The Mg content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 2.00 mass% or less, preferably 0.05 to 2.00 mass%, and more preferably 0.10 to 1.50 mass%. Mg is an additive element that causes age hardening by Mg2Si after bonding heating, and exhibits the effect of improving strength through this age hardening. When the Mg content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength of the fin material is increased. On the other hand, when the Mg content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, Mg reacts with the flux to form a compound with a high melting point, and as a result, the flux cannot act on the oxide film, making bonding extremely difficult.
[0075] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Cu. The Cu content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 1.50 mass% or less, preferably 0.05 to 1.50 mass%. Cu is an additive element that dissolves in the matrix to improve strength. When the Cu content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength of the fin material is increased. On the other hand, when the Cu content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, the corrosion resistance is reduced.
[0076] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Zn. The Zn content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 6.00 mass% or less, preferably 0.05 to 6.00 mass%. The addition of Zn is effective in improving corrosion resistance by sacrificial corrosion protection. Zn is almost uniformly dissolved in the matrix, but when a liquid phase is generated, it dissolves therein and the Zn in the liquid phase becomes concentrated. When the liquid phase seeps out to the surface, the Zn concentration in that part increases, so that the corrosion resistance is improved by the sacrificial anode action. In addition, by using the heat exchanger fin material according to the present invention as a fin material used in a heat exchanger, a sacrificial corrosion protection action that protects tubes and the like from corrosion can be exerted. When the Zn content of the aluminum alloy forming the heat exchanger fin material is within the above range, the fin material has an appropriate sacrificial corrosion protection action. On the other hand, when the Zn content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, the corrosion rate increases and the self-corrosion resistance decreases.
[0077] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Ti and / or V. The Ti content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. The V content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. Ti and V are dissolved in the matrix to improve the strength, and are distributed in layers to prevent the progress of corrosion in the plate thickness direction. By having the Ti or V content of the aluminum alloy forming the heat exchanger fin material within the above range, the strength is increased and the progress of corrosion in the plate thickness direction can be delayed. On the other hand, if the Ti or V content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, coarse crystals are generated, which inhibits the formability and corrosion resistance.
[0078] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Zr. The Zr content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. Zr precipitates as an Al-Zr intermetallic compound, and exerts an effect of improving the strength after joining by dispersion strengthening, and the Al-Zr intermetallic compound acts on the coarsening of crystal grains during heating. When the Zr content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength is increased. On the other hand, when the Zr content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, coarse intermetallic compounds are easily formed, and the plastic workability is reduced.
[0079] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Cr. The Cr content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. Cr improves strength by solid solution strengthening, and also acts to coarsen crystal grains after heating by precipitation of Al-Cr-based intermetallic compounds. When the Cr content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength is increased. On the other hand, when the Cr content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, coarse intermetallic compounds are easily formed, and the plastic workability is reduced.
[0080] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Ni. The Ni content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 2.00 mass% or less, preferably 0.05 to 2.00 mass%. Ni crystallizes or precipitates as an intermetallic compound, and exerts the effect of improving the strength after bonding by dispersion strengthening. When the Ni content of the aluminum alloy forming the heat exchanger fin material is within the above range, the strength is increased. On the other hand, when the Ni content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, coarse intermetallic compounds are easily formed, and the workability and self-corrosion resistance are reduced.
[0081] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain Sn and / or In. The Sn content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. The In content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.30 mass% or less, preferably 0.05 to 0.30 mass%. Sn and In have the effect of exerting a sacrificial anode function. When the Sn or In content of the aluminum alloy forming the heat exchanger fin material is within the above range, the corrosion resistance of the heat exchanger is improved. On the other hand, when the Sn or In content of the aluminum alloy forming the heat exchanger fin material exceeds the above range, the corrosion rate increases and the self-corrosion resistance decreases.
[0082] The aluminum alloy forming the heat exchanger fin material according to the present invention may contain one or more elements selected from Be, Sr, Bi, Na, and Ca. The Be content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.10 mass% or less, preferably 0.001 to 0.10 mass%. The Sr content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.10 mass% or less, preferably 0.001 to 0.10 mass%. The Na content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.10 mass% or less, preferably 0.001 to 0.10 mass%. The Ca content of the aluminum alloy forming the heat exchanger fin material according to the present invention is 0.05 mass% or less, preferably 0.001 to 0.05 mass%. These trace elements can improve the bondability by finely dispersing Si particles and improving the fluidity of the liquid phase. The aluminum alloy forming the heat exchanger fin material has a Be, Sr, Bi, Na or Ca content in the above range, which enhances the bondability. On the other hand, if the aluminum alloy forming the heat exchanger fin material has a Be, Sr, Bi, Na or Ca content in excess of the above range, it may cause problems such as reduced corrosion resistance. In addition, whether one selected from Be, Sr, Bi, Na and Ca is added, or two or more are added, each element is added within the above range.
[0083] The heat exchanger fin material according to the present invention may be produced by any method, and is produced, for example, by the method described below.
[0084] When an aluminum alloy ingot is cast using a DC (Direct Chill) casting method, the casting speed of the slab during casting is controlled as follows. The casting speed affects the cooling rate, so it is set to 20 to 100 mm / min. If the casting speed is less than 20 mm / min, a sufficient cooling rate cannot be obtained, and the crystallized intermetallic compounds, such as Si-based intermetallic compounds and Al-Fe-Mn-Si-based intermetallic compounds, become coarse. On the other hand, if the casting speed exceeds 100 mm / min, the aluminum material does not solidify sufficiently during casting, and a normal ingot cannot be obtained. The casting speed is preferably 30 to 80 mm / min. The thickness of the ingot (slab) during DC continuous casting is preferably 600 mm or less. If the slab thickness exceeds 600 mm, a sufficient cooling rate cannot be obtained and the intermetallic compounds become coarse. A more preferable slab thickness is 500 mm or less. After producing the slab by the DC casting method, homogenization, hot rolling, cold rolling, and annealing are performed as necessary, which are usually performed, to obtain the heat exchanger fin material according to the present invention. In addition, tempering is performed according to the application. This tempering is usually performed as H1n or H2n to prevent erosion, but soft material (O material) may be used depending on the shape and usage method.
[0085] The heat exchanger fin material according to the present invention can also be manufactured by a continuous casting method. In that case, the manufacturing method is not particularly limited as long as it is a method for continuously casting a plate material, such as a twin-roll continuous casting and rolling method or a twin-belt continuous casting method. The twin-roll continuous casting and rolling method is a method in which molten aluminum is supplied between a pair of water-cooled rolls from a refractory hot water supply nozzle, and a thin plate is continuously cast and rolled, and examples of such a method include the Hunter method and the 3C method. The twin-belt continuous casting method is a continuous casting method in which molten metal is poured between rotating belts that are opposed to each other above and below and are water-cooled, and the molten metal is solidified by cooling from the belt surface to form a slab, and the slab is continuously drawn out from the side of the belt opposite to the pouring side and wound into a coil shape. In the twin-roll continuous casting and rolling method, the cooling rate during casting is several to several hundred times faster than that in the DC casting method. For example, the cooling rate in the DC casting method is 0.5 to 20°C / sec, while the cooling rate in the twin-roll continuous casting and rolling method is 100 to 1000°C / sec. Therefore, the dispersed particles generated during casting are characterized by being finer and more densely distributed than in DC casting. These dispersed particles distributed at high density react with the matrix surrounding the dispersed particles during bonding, making it easier to generate a large amount of liquid phase, which results in good bondability. The speed of the rolled plate when casting using the twin-roll continuous casting rolling method is preferably 0.5 m / min or more and 3 m / min or less. The casting speed affects the cooling rate. If the casting speed is less than 0.5 m / min, a sufficient cooling rate cannot be obtained and the compounds become coarse. Also, if the casting speed exceeds 3 m / min, the aluminum material does not solidify sufficiently between the rolls during casting, and a normal plate-shaped ingot cannot be obtained. The molten metal temperature when casting by the twin-roll continuous casting rolling method is preferably in the range of 650 to 800°C. The molten metal temperature is the temperature of the head box located immediately before the hot water supply nozzle. If the molten metal temperature is less than 650°C, giant dispersed particles of intermetallic compounds are generated in the hot water supply nozzle, and these particles are mixed into the ingot, causing the plate to break during cold rolling. If the molten metal temperature exceeds 800°C, the aluminum material does not solidify sufficiently between the rolls during casting, and a normal plate-shaped ingot cannot be obtained. A more preferable molten metal temperature is 680 to 750°C. The thickness of the cast plate is preferably 2 mm to 10 mm. In this thickness range, the solidification rate in the center of the plate is fast, and a uniform structure is easily obtained. If the cast plate thickness is less than 2 mm, the amount of aluminum passing through the casting machine per unit time is small, making it difficult to stably supply the molten metal in the plate width direction. On the other hand, if the cast plate thickness exceeds 10 mm, it becomes difficult to wind the plate with a roll. A more preferable cast plate thickness is 4 mm to 8 mm. The obtained cast plate material is rolled to a final plate thickness to obtain the heat exchanger fin material according to the present invention. During the process of rolling to the final plate thickness, annealing may be performed one or more times. Appropriate tempering is selected depending on the application. Normally, H1n or H2n tempering is used to prevent erosion, but annealed material (O material) may be used depending on the shape and method of use.
[0086] The heat exchanger of the present invention is obtained by combining the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and a component such as a header that is combined as necessary, and then heating the resulting combination at a temperature at which the liquid phase rate of the fin material is 5.0% to 35.0%. The heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention are bonded to each other. The heat bonding conditions when heating the combination of the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and a component such as a header that is combined as necessary are preferably such that the region of 400°C or higher is heated at an average heating rate of 10°C / min, and the temperature is kept at 590 to 610°C, preferably 600°C, for 3 minutes, and then cooled to 100°C or lower. The heating atmosphere during heat bonding is not particularly limited. Since Si affects the solidus temperature, the heating temperature when heat bonding the combination of the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and a component such as a header that is combined as necessary is appropriately selected depending on the Si content. In addition to Si, Zn and Cu also affect the solidus temperature. Therefore, when the heat exchanger fin material of the present invention contains Zn and / or Cu in addition to Si, the heating temperature when heat-bonding the combination of the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and components such as headers that are combined as necessary is appropriately selected depending on the content of Si, Zn and / or Cu.
[0087] The heat exchanger of the present invention is heat-bonded using a fin material having a heat-bonding function in a single layer, so the fillet cross-sectional area formed between the fin and the tube is smaller than that of a heat exchanger using a brazing sheet clad with a brazing material. In the heat exchanger of the present invention, the Zn content of the Zn-containing film formed on the surface of the tube material is 1.0 to 4.5 g / m 2Since this is set within an appropriate range, Zn concentration in the fillet is suppressed, and the fillet potential does not become the most base potential, or even if it does become the most base potential, the potential difference with other parts is within 40 mV. This prevents preferential corrosion of the fillet and ensures the corrosion resistance and heat exchange performance of the core for a long period of time.
[0088] The heat exchanger of the present invention is obtained by combining the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and a component to be combined as necessary, such as a header, and then heating the resulting combination at a temperature at which the liquid phase ratio of the fin material is 5.0% to 35.0%, thereby joining the heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention. The heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention are the same as those described above.
[0089] That is, the heat exchanger of the present invention is a heat exchanger having an aluminum alloy tube through which a working fluid flows, and an aluminum alloy fin metallically joined to the tube, At least, a tube body made of an aluminum alloy and a ferrite layer formed on the outer surface of the tube body, the ferrite layer having an atomic ratio of 1.0 to 4.5 g / m 2 and a Zn-containing film containing Zn, and a heat exchanger fin material made of an aluminum alloy and having a single-layer thermal bonding function at a temperature at which the liquid phase ratio of the heat exchanger fin material is 5.0% or more and 35.0% or less, and then the resulting combination is heated at a temperature at which the liquid phase ratio of the heat exchanger fin material is 5.0% or more and 35.0% or less to bond the heat exchanger tube material and the heat exchanger fin material. This is a heat exchanger characterized by the above.
[0090] The heating temperature when heat-bonding the combination of the heat exchanger tube material according to the present invention, the heat exchanger fin material according to the present invention, and the components such as a header that are combined as necessary is a temperature at which the liquid phase rate of the fin material is 5.0% to 35.0%, and the heat-bonding conditions are preferably such that the region of 400°C or higher is heated at an average heating rate of 10°C / min, and the temperature is kept at 590 to 610°C, preferably 600°C, for 3 minutes, and cooled to 100°C or lower. Since Si affects the solidus temperature, the heating temperature when heat-bonding the combination of the heat exchanger tube material according to the present invention, the heat exchanger fin material according to the present invention, and the components such as a header that are combined as necessary is appropriately selected depending on the Si content. In addition to Si, Zn and Cu also affect the solidus temperature. Therefore, when the heat exchanger fin material of the present invention contains Zn and / or Cu in addition to Si, the heating temperature when heat-bonding the combination of the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and components such as headers that are combined as necessary is appropriately selected depending on the content of Si, Zn and / or Cu.
[0091] In addition, the method for producing a heat exchanger of the present invention includes combining the heat exchanger tube material of the present invention, the heat exchanger fin material of the present invention, and a component to be combined as necessary, such as a header, and then heating the resulting combination at a temperature at which the liquid phase ratio of the fin material is 5.0% or more and 35.0% or less, thereby joining the heat exchanger tube material of the present invention and the heat exchanger fin material of the present invention, and performing a heat exchange. vessel The heat exchanger tube material according to the present invention and the heat exchanger fin material according to the present invention are the same as those described above.
[0092] The present invention will be specifically described below by showing examples, but the present invention is not limited to the examples shown below. EXAMPLES
[0093] (Reference Examples and Comparative Examples) An extruded tube material was produced using an alloy having the chemical composition shown in Table 1. Fin materials were also produced using an alloy having the chemical composition shown in Table 2. Then, using the obtained tube materials and fin materials, a mini-core simulating a heat exchanger as shown in Fig. 5 was assembled and heat-bonded, and the corrosion resistance of the obtained mini-core was evaluated.
[0094] (Examples 1 to 3, Comparative Examples 1 to 2) <Preparation of tube material> A billet having the chemical composition shown in Table 1 was heated at 600°C for 10 hours for homogenization. After the homogenization process was completed, the billet was cooled to room temperature, reheated to 500°C, and hot extrusion was performed. As a result, a tube body was produced that had a flat cross section perpendicular to the extrusion direction and was equipped with multiple refrigerant flow paths. Next, Zn was applied to the surface of the tube body so that the Zn content of the Zn-containing film was the amount shown in Table 3. In the tube materials of Examples 1 to 3, a paint containing flux powder made of a K-Zn-F compound was applied to the flat surface of the tube body using a roll coater, and then dried. In the tube materials of Comparative Examples 1 and 2, Zn was sprayed on the surface of the tube body immediately after extrusion. In Table 3, the Zn content of the Zn-containing film is the content before heat bonding.
[0095] <Making the fins> The alloy composition shown in Table 2 was cast into a plate with a thickness of 6 mm by continuous casting, and then intermediate annealing was performed to soften the material, and the plate thickness was reduced to 0.20 mm by cold rolling, and final annealing was performed to prepare the test material. The obtained plate was subjected to corrugation processing to produce a fin material with a corrugated shape. The fin pitch was 3 mm and the fin height was 10 mm.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Table 3]
[0099] (Examples 4 to 6, Comparative Examples 3 to 4) <Mini core assembly> The fin material was laminated with the top and bottom sandwiched between the tube material, and assembled into the specified shape shown in Figure 5. The tube material and fin material were heated and bonded in this state to obtain a mini-core simulating a heat exchanger. The heating was performed in a nitrogen gas atmosphere, and the tube material and fin material were heated to 600°C at an average heating rate of 10°C per minute in the region above 400°C, and the temperature of 600±3°C was maintained for 3 minutes, after which the temperature was lowered to room temperature. The five mini-cores (test pieces 1 to 5) obtained in this manner were used to evaluate corrosion resistance. The results are shown in Table 4. Based on the composition of fin material B, the liquid phase ratio of fin material B at 600°C was determined by the method described in this specification and was calculated to be 16.6%.
[0100] <Corrosion resistance evaluation> The SWAAT test specified in ASTM-G85-AnnexA3 was carried out on each specimen for 960 hours. After the test, the specimens were visually inspected to determine whether the fins had peeled off. In addition, a leak check was performed to confirm whether the tube had penetrated the specimen.
[0101] [Table 4]
[0102] In all of Examples 4 to 6 and Comparative Examples 3 and 4, no corrosion penetration of the tube occurred. In addition, in Examples 4 to 6, preferential corrosion of the fillet and early fin loss did not occur, and excellent corrosion resistance was demonstrated even in a severe corrosive environment. On the other hand, in Comparative Examples 3 and 4, preferential corrosion occurred in the fillets, and the fins fell off early, resulting in poor corrosion resistance.
Claims
1. A heat exchanger having an aluminum alloy tube through which a working fluid flows and an aluminum alloy fin metallically joined to the tube, The tube is made of an aluminum alloy and has a tube body and a thickness of 1.0 to 4.5 g / m2 formed on the outer surface of the tube body. 2 and a Zn-containing membrane not containing Si, The Zn-containing film contains a flux powder made of a Zn-containing compound or a pure Zn powder, The fin is made of an aluminum alloy and is formed using a heat exchanger fin material having a single layer thermal bonding function at a temperature at which the liquid phase ratio is 5.0% or more and 35.0% or less. A heat exchanger characterized by:
2. 2. The heat exchanger according to claim 1, characterized in that the aluminum alloy forming the tube body contains 0.10 to 1.20 mass% Mn, a Ti content of 0.10 mass% or less, and the remainder being Al and unavoidable impurities.
3. 3. The heat exchanger according to claim 2, characterized in that the aluminum alloy forming the tube body further contains one or more elements selected from the group consisting of 0.60 mass% or less of Cu, 0.70 mass% or less of Si, and 0.50 mass% or less of Fe.
4. 4. The heat exchanger according to claim 1, wherein the flux powder is made of a K-Zn-F based compound.
5. The heat exchanger fin material is an aluminum alloy containing 1.00 to 5.00 mass% Si, 0.05 to 2.00 mass% Mn, an Fe content of 2.00 mass% or less, and the remainder being Al and unavoidable impurities. The heat exchanger according to any one of claims 1 to 4, characterized in that the aluminum alloy forming the heat exchanger fin material contains 1.00 to 5.00 mass% Si, 0.05 to 2.00 mass% Mn, an Fe content of 2.00 mass% or less, and the remainder being Al and unavoidable impurities.
6. The aluminum alloy forming the heat exchanger fin material further contains one or more selected from 2.00 mass% or less of Mg, 1.50 mass% or less of Cu, 6.00 mass% or less of Zn, 0.30 mass% or less of Ti, 0.30 mass% or less of V, 0.30 mass% or less of Zr, 0.30 mass% or less of Cr, and 2.00 mass% or less of Ni. The heat exchanger according to claim 5, characterized in that it contains one or more selected from the group consisting of 2.00 mass% or less of Mg, 1.50 mass% or less of Cu, 6.00 mass% or less of Zn, 0.30 mass% or less of Ti, 0.30 mass% or less of V, 0.30 mass% or less of Zr, 0.30 mass% or less of Cr, and 2.00 mass% or less of Ni.
7. The heat exchanger according to claim 5 or 6, characterized in that the aluminum alloy forming the heat exchanger fin material further contains one or more selected from 0.30 mass% or less of Sn, 0.30 mass% or less of In, 0.10 mass% or less of Be, 0.10 mass% or less of Sr, 0.10 mass% or less of Bi, 0.10 mass% or less of Na, and 0.50 mass% or less of Ca.
8. The heat exchanger tube material according to claim 1, A tube material body is made of an aluminum alloy containing 0.10 to 1.20 mass % of Mn, a Ti content of 0.10 mass % or less, and the balance being Al and unavoidable impurities, and a layer is formed on the outer surface of the tube material body, and the layer has an atomic ratio of 1.0 to 4.5 g / m 2 and a Zn-containing film not containing Si, The Zn-containing film comprises a flux powder made of a compound containing Zn, or a pure Zn powder.
9. 9. The heat exchanger tube material according to claim 8, further comprising one or more elements selected from the group consisting of 0.60 mass % or less of Cu, 0.70 mass % or less of Si, and 0.50 mass % or less of Fe.
10. 10. The heat exchanger tube material according to claim 8, wherein the flux powder is made of a K-Zn-F based compound.
11. A heat exchanger having an aluminum alloy tube through which a working fluid flows and an aluminum alloy fin metallically joined to the tube, At least, a tube body made of an aluminum alloy and a ferrite layer formed on the outer surface of the tube body, the ferrite layer having an atomic weight of 1.0 to 4.5 g / m 2 a Zn-containing film containing Zn and no Si, the Zn-containing film containing a flux powder made of a compound containing Zn or a pure Zn powder; a heat exchanger fin material made of an aluminum alloy and having a thermal bonding function in a single layer at a temperature at which a liquid phase ratio is 5.0% or more and 35.0% or less; and then heating the resulting combination at a temperature at which the liquid phase ratio of the heat exchanger fin material is 5.0% or more and 35.0% or less to bond the heat exchanger tube material and the heat exchanger fin material. A heat exchanger comprising:
Citation Information
Patent Citations
Tube for heat exchanger and method for manufacturing heat exchanger
JP2019168145A
Heat exchanger tube
WO2011090059A1
Aluminum alloy material and aluminum alloy structure and production process therefor
WO2013080650A1
Process for producing aluminum alloy tube having sacrificial anticorrosion layer and joining layer
WO2014020722A1
Heat exchanger, and fin material for said heat exchanger
WO2014196183A1